(untitled) (Innovative professional education, 2025)
The article defines the role of today’s master of vocational training. The main methods of organizing students’ cognitive activity are described. It is indicated that visual and practical methods of conveying information are the most effective. The article determines the necessity and expediency of implementing digital technologies in industrial training lessons for «Instrumentation and Automation Control Mechanics»